Implementasi Nilai Nilai Lokal Wisdom Untuk AUD Melalui Kesenian Lengger Wonosobo - Anik Klara Novyana; Anisa Saputri; Namira Kurnia; Restiara Dinda Arysta; Hidayatu Munawaroh (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2023)
The Rhymes of Parikan Tari Topeng Lengger is one of the oral literature in Wonosobo. This research will discuss the values of local wisdom in the Parikan Tari Topeng Lengger Wonosobo. The study PIAUD on oral literature is interesting since the Parikan Tari Topeng Lengger Wonosobo has many values of local wisdom of the supporting community, which are still relevant to the current digital era. As long as we know that no other researcher studies on Parikan Tari Topeng Lengger Wonosobo. The objective of this study is to find and describe the values of local wisdom in the Parikan Tari Topeng Lengger Wonosobo. The researcher uses a descriptive method to analyze the Parikan Tari Topeng Lengger Wonosobo. This is explanatory research. It uses an objective approach. The theory relevant to this research is the local wisdom theory. In short, the category of noble values in the oral tradition has four relations: (1) the relation to God, (2) people and its social community, (3) people to nature, and (4) people to themselves.